The Use of Works of Musical Art in Preschool Education: A Slovak Perspective - Ivana Rochovská, Eva Dolinská, Božena Švábová (Educational Process: International Journal)
Background/purpose – Musical art has great potential for developing a child’s personality. Research around the world confirms that the inclusion of musical art stimuli has a positive impact on preschool children and brings multiple benefits. However, it needs to be led by a teacher who is competent pedagogically, but who is also equally competent artistically. The aim of the research was to examine the use of works of musical art in preschool education in Slovakia from the perspective of preschool teachers.